MONITORING PENYAKIT BLAS PADI DI AGROEKOSISTEM RAWA KALIMANTAN TENGAH - Yuliani, Dini; Santoso, Santoso; Anggara, Agus Wahyana (Agroswagati : Jurnal Agronomi, 2022)
Blast disease caused by Pyricularia oryzae is one of the primary diseases that can reduce rice production in Indonesia. This disease has spread in almost all agroecosystems, including swamps. This study aimed to obtain information on the incidence and severity of blast disease based on routine monitoring for rice blast disease control strategies in swamp agroecosystems in Central Kalimantan. The blast disease incidence and severity were observed from the early vegetative phase, flowering, and grain ripening until before harvest. Observations were made at the sample point of the same rice clump with an area of 14 ha at the display location of rice varieties and 66 ha at the rice demfarm. The blast incidence in the presence or absence of blast symptoms in the observed clump, while the severity of disease in the form of severe and low damage to the clump was observed using a scoring method that refers to the Standard Evaluation System for Rice from IRRI. Incidence and severity of blast disease at the varieties display and rice demfarm location in Blanti Siam village, Pandih Batu Sub-District, Pulang Pisau District Central Kalimantan was relatively low. In September, blast disease incidence and severity were still low when rice plants were in the vegetative phase. Blast disease incidence and severity increase in October when the plant enters the generative phase. The incidence of the disease decreased in November. Leaves showing blast symptoms ran into leaf death, and blast pathogens did not infect new leaves, so rice blast symptoms were not found or in low conditions.